Skin autofluorescence Is associated With low bone mineral density in type 2 diabetic patients - YAVUZ, DİLEK; APAYDIN, TUĞÇE (My University, 2021)
Although the risk of bone fracture is increased in type 2 diabetes (T2DM), bone mineral density (BMD) is increased rather than decreased. Accumulation of advanced glycation end products (AGEs) adversely influences the fracture resistance of bone in T2DM. We hypothesized that SAF is also associated with BMD levels in type 2 diabetic patients and aimed to evaluate the association of SAF with BMD and the presence of osteoporosis. This cross-sectional case-control study included 237 patients with T2DM (F/M: 133/104, 56.2±11.9 yrs) and 100 age- and sex-matched controls (F/M: 70/30, 54.8±8.8 yrs). Skin autofluorescence, a validated non-invasive measure of tissue AGEs, is used to detect the accumulation of AGEs in skin collagen using AGE Reader (DiagnOptics B.V., Groningen, The Netherlands). In addition, BMD was measured with DEXA (Lunar DPX-L). Patients with T2DM had higher SAF values compared to control group (2.21±0.53 AU vs. 1.79±0.33 AU, p < 0.001). Male subjects had higher SAF compared to women (2.34±0.53 AU vs. 2.11±0.50 AU, p < 0.001). Subjects with below -2.5 femoral neck or lumbar T scores had higher SAF measurements compared to subjects with normal T scores (2.46±0.53 AU vs. 2.18±0.52 AU, p = 0.006). Femoral neck BMD was lower in subjects with T2DM (0.946±0.345 g/cm2 vs. 1.005±0.298 g/cm2, p = 0.002). There was a negative correlation between SAF and femoral neck BMD (r=-0.24, p < 0.001), femoral neck T scores (r=-0.24, p < 0.001), L1-4 BMD (r=-0.10, p = 0.005), L1-4 T score (r=-0.16, p=0.001) and a positive correlation between SAF and age (r=0.44, p < 0.001), body mass index (r:0.16, p = 0.002) and HbA1c (r=0.37, p < 0.001). Accumulation of skin AGEs was increased, and BMD levels were decreased in diabetic patients. A negative association between SAF and BMD was detected, indicating a relationship between higher AGE accumulation and low BMD and osteoporosis in diabetic patients. Long-term prospective studies are needed to identify the practical use of SAF measurement in diabetic bone disease.
Keywords: type 2 diabetes; Advanced glycation end-products; Bone mineral density; skin autofluorescence